The Impact of Moringa Leaf Capsule Supplementation on Weight Change in Adolescent Girls Who Drop Out of School Aged 12–18 Years - Astri Yuliandini; Dwi Ghita; Ani Ani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Complex health issues require collaboration from various healthcare professions. One key aspect of preparing a healthy generation is nutritional status. Moringa leaves (Moringa oleifera), known as the “miracle tree,” are rich in essential nutrients such as vitamins, proteins, iron, carbohydrates, fats, minerals, and amino acids. This study aimed to evaluate the impact of Moringa leaf extract capsules on weight gain among adolescent girls who dropped out of school in North Polongbangkeng District, Takalar Regency, South Sulawesi. This true experimental study used a Randomized Controlled Double Blind Pre-Posttest design. A total of 30 school dropouts aged 12–18 years were selected using simple random sampling, then randomly assigned into an intervention group (15 received Moringa capsules, 2×1 daily, 1000 mg/capsule) and a control group (15 received iron tablets with the same dose). Data were analyzed using the Paired T-Test and Mann-Whitney U test. The intervention group showed a significant weight increase from 41.82 kg to 42.42 kg (p < 0.05), while the control group showed no significant change. There was a significant difference between groups (p = 0.001). Moringa leaf extract significantly improved weight gain among adolescent girls who dropped out of school.